1999
DOI: 10.1080/10273660008833056
|View full text |Cite
|
Sign up to set email alerts
|

Repopulation of Tumour Cells during Radiotherapy Is Doubled during Treatment Gaps

Abstract: The aim of this work is to analyse the proliferation of tumour cells in the treatment gapduring the radiotherapy for head neck cancer.Material and Methods: The clinical material is based on records of head and neck patients treated by radiotherapyalone in our institution. The effect of radiotherapy was assumed to be described by a linearquadratic model. The patient data were fitted directly to the radiobiological model and theparameters were estimated using maximum-likelihood procedures.Results: According to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Así, uno de los motivos descritos para explicar los abandonos del tratamiento radioterápico es la incapacidad de soportar los efectos adversos de la radioterapia (14,15). Se ha notificado que esta falta de control del dolor puede por tanto reducir los posibles beneficios de la radioterapia (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Así, uno de los motivos descritos para explicar los abandonos del tratamiento radioterápico es la incapacidad de soportar los efectos adversos de la radioterapia (14,15). Se ha notificado que esta falta de control del dolor puede por tanto reducir los posibles beneficios de la radioterapia (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionunclassified
“…Este fenómeno se encuentra bien documentado en pacientes con carcinoma de células escamosas de cabeza y cuello, así como en otros tipos de cáncer (16)(17)(18)(19)24). Así, se ha estimado que la tasa de repoblación durante un cese del tratamiento es casi cuatro veces más rápida que durante los días de irradiación (20,21). Asimismo, se ha estimado que al alargar el tiempo de radioterapia en un día el control local se reduce en un 1,4-1,7% cada día (16,22).…”
Section: Discussionunclassified
“…treatment gaps) in radiotherapy delivery can significantly compromise treatment success, local tumour control and overall survival. 91,[93][94][95][96] According to Nagar and Formenti, 91 delaying the start of adjuvant radiotherapy over 8 weeks after surgery will double the risk of local recurrence in breast cancer patients and every week of radiotherapy delay beyond 2 weeks after surgery for high-grade gliomas patients increases the risk of death by 8•9%. Several studies have reported a significant impact of the COVID-19 pandemic on radiotherapy delivery in several cancer centres.…”
Section: Radiation Therapymentioning
confidence: 99%
“… 6 , 7 Such poor pain control has been reported to impact a patient’s willingness to attend treatment and to affect their ability to complete a course of treatment without interruptions, which in turn would impact the potential benefits of radiotherapy. 8 , 10 13 , 15 17 , 27 …”
Section: Conclusion and Potential Implicationsmentioning
confidence: 99%
“… 8 , 11 14 The repopulation rate during a treatment gap was estimated to be nearly four times faster than that during irradiation days. 15 , 16 One extra day of prolonged treatment of radiotherapy was estimated to reduce local control by 1.4% to 1.7% each day. 8 , 17 In another study, each day of interruption of radiotherapy was estimated to increase the hazard rate by 3.3% for local and regional tumor control, and by 2.9% for disease-free survival.…”
Section: Introductionmentioning
confidence: 99%